Odpowiedź :
e)
[tex]\frac{4x + 4}{5} = \frac{9x - 9}{4}[/tex] | * 20
4 (4x +4) = 5(9x - 9)
16x + 16 = 45x - 45
61 = 29x | ÷ 29
x = [tex]\frac{61}{29}[/tex] = [tex]2\frac{3}{29}[/tex]
f)
[tex]\frac{64+8x}{7} = 3x - \frac{3}{8}[/tex] | * 56
512 + 64x = 168x - 21
533 = 104x | ÷104
x = [tex]\frac{533}{104}[/tex] = 5[tex]\frac{13}{104}[/tex] = [tex]5\frac{1}{8}[/tex]
g)
[tex]\frac{-12x + 80}{6} = \frac{-1-11x}{4}[/tex] | * 24
-48x + 320 = -6 -66x
18x = -326 | ÷ 18
x = [tex]-\frac{326}{18}[/tex] = [tex]-18\frac{1}{9}[/tex]
h)
[tex]\frac{2x -6 -9 +3x}{3} = \frac{-x-4}{2}[/tex] | * 6
4x - 12 - 18 + 6x = -3x -12
13x = 18 | ÷13
x = [tex]\frac{13}{18}[/tex]
Odpowiedź:
e)
[2 * (2x + 2)]/5 = [3 * (3x - 3)]/4
2/5 * (2x + 2) = 3/4 * (3x - 3)
4/5x + 4/5 = 9/4x - 9/4
0,8x - 2 1/4x = -2 1/4 - 4/5
0,8x - 2,25x = -2,25 - 0,8
-1,45x = -3,05 /:(-1,45)
x = 305/100 : 145/100 = 305/100 * 100/145 = 61/29 = 1 3/29
f)
8 * (8 + x)/7 = 3(x - 1/8)
8/7 * 8 + 8/7x = 3x - 1/8
9/7x - 3x = -1/8 - 64/8
1 2/7x - 3x = -65/8
-1 5/7x = -65/8
-12/7x = -65/7 /*(-7/12)
x = 65/7 * 7/12 = 65/12 = 5 5/12
g)
-4 * (3x - 20)/6 = (-1 - 11x)/4
-2/3(3x - 20) = -1/4 - 11/4x
-2x + 40/3 = -1/4 - 11/4x
-2x + 2 3/4x = -1/4 - 13 1/3
3/4x = -3/12 - 13 4/12 /*4/3
x = -13 7/12 * 4/3 = -163/12 * 4/3 = -163/9 = -18 1/9
h)
[2 * (x - 3) - 3 * (3 - x)]/3 = -(x + 4)/2
(2x - 6 - 9 + 3x)/3 = -1/2x - 2
2/3x - 15/3 + x = -1/2x - 2
1 2/3x + 1/2x = -2 + 5
1 4/6x + 3/6x = 3
1 7/6x = 3
13/6x = 3 /*6/13
x = 3 * 6/13 = 18/13 = 1 5/13
Szczegółowe wyjaśnienie: